IMPLEMENTASI METODE SIMPLE ADDITIVE WEIGHTING DALAM PEMILIHAN JASA PENGIRIMAN BARANG - Paulina Kota; Adi Nugroho (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2024)
The restrictions imposed by the government to prevent the spread of COVID-19 have had significant impacts, particularly on the economic sector, leading many companies and small shops to close their businesses. This situation has changed shopping habits, especially among students who use e-commerce platforms in collaboration with delivery service companies to meet personal needs. However, many items ordered through delivery services do not meet expectations upon arrival, such as damaged goods, lost items, and deliveries that do not match the estimated time. The purpose of this research is to create a calculation within the decision-making system that can assist students in making accurate and fast decisions using the SAW method. The data collection was conducted by distributing questionnaires to 100 respondents who are students and have used delivery services. Based on the results obtained using the SAW method, J&T Express ranked first with the highest final score of 0.881, followed by JNE in second place with a final score of 0.765. Next, in third place is SiCepat with a final score of 0.599, Ninja Express in fourth place with a final score of 0.291, POS Indonesia in fifth place with a final score of 0.238. Then, in sixth place is TIKI with a final score of 0.166, and finally, Lion Parcel ranked seventh with a final score of 0.124.